El Mercurio Lies, and la Tercera Lies More: Political Bias in Newspaper Headlines in Chile, 1994-2010 - Osorio-Flores, R (2015)
In this article we examine the presence of bias in Chile s two main daily newspapers, El Mercurio and La Tercera, both of which have historically been associated with the political right. We analyse their principal headlines in the first 100 days of rule of presidents Eduardo Frei (1994-2000), Ricardo Lagos (2000-2006), Michelle Bachelet (2006-2010) and Sebastián Piñera (2010-2014). We find that La Tercera was more critical of all these presidents than El Mercurio. In La Tercera we also identify an ideological bias in favour of Piñera as compared to the centre-left presidents, and in El Mercurio a greater bias against Bachelet than the other presidents. © 2015 The Authors.